Variability of physics-based simulated ground motions in Thessaloniki urban area and its implications for seismic risk assessment - Lin, J.; Smerzini, C. (Frontiers in Earth Science, 2022)
An accurate characterization of earthquake ground motion and its variability is crucial for seismic hazard and risk analysis of spatially distributed portfolios in urban areas. In this work, a 3D physics-based numerical approach, based on the high-performance spectral element code SPEED (http://speed.mox.polimi.it/), is adopted to generate ground shaking scenarios for strong earthquakes (moment magnitude MW=6.5-7) in the Thessaloniki area (Northern Greece). These simulations account for kinematic finite-fault rupture scenarios and a 3D seismic velocity including the two main geological structures present in the area (Thessaloniki and Mygdonia basins). The numerical model is successfully validated by comparing simulated motions, on the one hand, with the recordings of a real small-magnitude (MW4.4) earthquake and, on the other, with empirical Ground Motion Models (GMMs) for the historical MW6.5 1978 earthquake. The sensitivity of results to the velocity model, anelastic attenuation, and non-linear soil effects is evaluated. The variability of the ground motion intensity measures in Thessaloniki as a function of the finite-fault rupture realizations (causative fault, magnitude, hypocenter location) is explored to gain insight into its potential impact on seismic risk assessment in urban areas.